Film Propaganda: Ikonografi Kekuasaan - Budi Irawanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
As a modern technological invention cinema has numerous potentialities such as economic, social and political power. Fascist regimes as well as film corporations have employed cinema as a tool of propaganda to control and mobilize the masses for the sake of their power longevity. Moreover, the character of film itself is a perfect fascist medium which came from the network of proto-fascism of the twentieth century civilization. By using various genres of Indonesian cinema from different eras as a case study, this article argues that Indonesian propaganda films have monolithic representation which can be described as a cult of "bapakisme" (patronism), "kultur komando" (command culture), marginalisation of women' role in Indonesian revolutionary movement and demonization of progressive women organisation, and glorification of the role of Soeharto in Indonesian revolutionary movement.